Average optimal stationary policies and linear programming in countable space Markov decision processes - Lasserre, J.B. (IEEE Conference on Decision and Control, 1992)
Average optimal stationary policies in countable space Markov decision processes and optimal solutions of an associated infinite dimensional linear program are discussed. Using the theory of linear programming in abstract spaces, sufficient conditions for the existence of optimal solutions are presented, and some previous ones are interpreted.< >